The activity approach to the psychological support of the 1st year university students - Natalia A. Rozhdestvenskaya (Национальный психологический журнал, 2017)
The paper is devoted to approbating the method of negative emotion processing as the main component of the psychological support of the first-year students experiencing difficulties in adapting to university life. Many teachers associate the gradual development of intellectual activity and knowledge with teaching of school subjects. The work of P.Ya. Galperin’s disciples and followers (e.g. O.Karabanova, A.Liders, Yu.Frolov, N. Rozhdestvenskaya) showed that the scientific method is universal and can be used to develop and improve various mental properties and activities. Using method «Perfection of Interpersonal Cognition Strategies» in psychological counseling based on P.Ya. Galperin’s theory promotes the development of adolescent reflexive mechanisms of understanding the personal characteristics of people, reducing the number of interpersonal conflicts with peers and adults, and also improving teachers’ understanding of the student personal characteristics. There are conditions under which the efficacy of mastering knowledge and cognitive skills are achieved. The educational experiment of studying the adaptation to university conditions in rural school graduates shows that mastering the cognitive processing of negative emotional experiences plays a leading role in the psychological adaptation of students. This method is an independent variable with respect to the three dependent ones, i.e. psychological adaptation in general, self-regulation of behaviour and communicative competence. The educational experiment carried out in accordance with the requirements of P.Ya. Galperin’s theory once again confirmed the high efficiency of P.Ya. Galperin’s methodology and showed that its potential capabilities are far from exhausted.